Production and Characterisation of Peroxidase from Aspergillus terrens Isolated from Water Sample in Wukari, Taraba State, Nigeria - Timothy, Mgbede; Abah, Moses Adondua; Ayo, Victoria Ifeoluwa; Ahmed, Maryam Usman; Oyibo, Okpanachi Nuhu; Ijeomah, Nkechi Gift; Gbadebo, Adetoyi Moses; A, Ajala-Lawal R.; Najeeb, Aliyu Olamilekan; Morolake, Olabanji Martina; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
The use of biocatalysts like enzymes in the development of environmentally sustainable processes has been reported as an ecofriendly approach for the current bioeconomy. This research aimed at producing and characterizing peroxidase from Aspergillus terrens isolated from water sample in Wukari, Taraba State, Nigeria. Fungi species from surface water sample obtained in Federal University Wukari, Taraba Nigeria were isolated through serial dilution of peptone water and was cultured in a room temperature in different petri dishes using Potato Dextrose Agar (PDA). A portion of the fungi growth chosen from the best growth of cultured water sample were cut and transferred into the 250 Erlenmeyer flask each containing an acceptable proportion of phosphate buffer, pH 6.0. The screening for peroxidase production was aseptically performed on a plate by inoculating the fermented medium with azur B dye. The appearance of a clear zone indicated a positive result for peroxidase activity. The incubation of the peroxidase enzyme was conducted over eleven days, with the highest enzyme yield observed on the eighth day. The results obtained in this study showed that the effect of pH on peroxidase activity was studied, revealing that the optimum pH for enzyme activity was 7.5. Peroxidase activity was lowest at pH 1. Temperature variation studies showed that the optimum temperature for peroxidase activity was 30°C. Peroxidase activity changed as substrate concentration was varied. Peroxidase activity was revealed to be highest at substrate concentration 1.9 mM. The kinetic parameters for peroxidase were investigated to be: Vmax = 10.57082; Km = 0.244186. The evidence presented in this research has shown that peroxidase can be produced in mass by using of white rot fungi from/around our surroundings and can be explored as a cheap source of peroxidase for industrial and biotechnological purposes. In conclusion, producing peroxidase from local isolates presents an eco-friendly and affordable alternative for industrial applications, contributing to environmental sustainability and public health.